Hypocalcaemia after an Occult Calcium Channel Blocker Overdose: A Case Report and Literature Review. (18th September 2013) - Price, David; Radke, Joshua; Albertson, Timothy
Abstract Hypocalcaemia is a rare complication of calcium channel blocker overdose, having been reported only once previously (J Toxicol Clin Toxicol, 1992, 30, 309). In this article, we report a case of a 37‐year‐old woman who developed hypocalcaemia after a verapamil overdose, review the literature and propose a mechanism for this rare finding.